Setting goals and self-actualization - Moris, Megawati (2019)
The first question is “how did I decide on this topic?” I happened to come across a video by Anthony Robbins who is a very well-known and by the way very wealthy motivational speaker from the US and listened to his talk on “setting goals.” If before I was cynical about Western motivational speakers who do not include God, religion and spirituality in their views, this time I paid attention and finished listening to what he had to say. His talk did strike a few chords in me. So tonight’s talk I would say is an Islamic version of some of the important points Anthony Robbins spoke about the topic of “setting goals.”